Unexplored avenues: a narrative review of cognition and mood in postmenopausal African women with female genital circumcision/mutilation/cutting - Rohina Kumar; Noelia Calvo; Gillian Einstein; Gillian Einstein; Gillian Einstein; Gillian Einstein; Gillian Einstein; Gillian Einstein (Frontiers in Global Women's Health)
Recent ageing research has projected the lifespan and proportion of postmenopausal women living in low- and middle-income countries to substantially increase over the years, especially on the African continent. An important subgroup within the African postmenopausal population is those with female genital circumcision/mutilation/cutting (FGC). Practised across 31 African nations, FGC holds cultural significance as it is deemed essential to marriage and successful womanhood. Perhaps because of this, most FGC studies have primarily focused on women's reproductive functioning and their mood experiences. These studies also usually exclude postmenopausal women from their cohorts. Consequently, cognition and age-related cognitive decline and preservation remain understudied. Therefore, we investigated what is known about mood and cognition in local and immigrant postmenopausal African women with FGC. To do this, we carried out a narrative review searching PubMed, PsycInfo, and Google Scholar databases. Boolean combinations of keywords related to FGC, cognition, ageing, and mood were used, with a focus on cognition and ageing-related terms. Only studies published in English, those that recruited African women with FGC aged 50 years and older, and those that investigated cognitive and/or mood-related experiences were included. Ten studies were found; these included quantitative, qualitative, and case reports. The age range of cohorts across included studies was 13–90 years; women who were likely postmenopausal formed a minority within the cohorts (4.5%–25%). There were no studies assessing memory or cognition beyond those looking at FGC-related memories, which were vivid, especially if women had type III FGC (Pharaonic) or were older at the time of FGC. Although most of these women reported experiencing negative emotions concerning FGC, quantitative reports showed that only a minority of women experienced post-traumatic stress disorder, anxiety, or depression. Thus, there remains an urgent need to bring this understudied group into ageing and dementia research. Future research should adopt mixed-methods with culturally sensitive methodologies to investigate the lived experience of ageing as well as cognitive changes. A holistic understanding of ageing women from the Horn of Africa's experiences and needs will support an improvement in the quality of care delivered to this cohort in both local and immigrant contexts.